From Dichotomy to Integration: Epistemological Transformation of Science and Religion in Science Learning from the Perspective of Philosophy of Science at MTS N 3 Kedir - Abas Shofwan; Ngainun Na’im (Sakura Digital Nusantara, 2026)
The persistent dichotomy between scientific knowledge and religious understanding remains a major challenge in Islamic education, particularly in Natural Science learning, where integration is often limited to symbolic references rather than meaningful epistemological reconstruction. This study aimed to examine the process of epistemological transformation through the integration of science and religion in Natural Science learning at MTsN 3 Kediri and to develop a conceptual model that explains this transformation. A qualitative case study design was employed using classroom observations, semi structured interviews with the principal, Natural Science teachers, Islamic Religious Education teachers, and students, as well as document analysis. Data were analyzed through thematic analysis following the stages of data reduction, coding, categorization, interpretation, and verification using source and method triangulation to ensure credibility. The findings indicate that epistemological transformation occurs through three interrelated dimensions, namely conceptual integration, methodological integration, and practical integration. The integration process shifts the educational paradigm from a dichotomous perspective toward a complementary and dialogical relationship between science and religion, supported by visionary leadership, teacher competence, institutional commitment, and a pesantren based educational environment. Based on these findings, this study proposes an epistemological transformation model that integrates scientific inquiry with Islamic values within a holistic learning framework. The study contributes to the discourse on science and religion integration by providing empirical evidence that epistemological transformation can be operationalized through classroom practice, institutional culture, and educational leadership. The proposed model offers practical guidance for developing integrative science education in Islamic schools while extending the theoretical perspective on the integration of scientific and religious knowledge.